SIPERBAKA: Situs Percandian Batujaya Karawang Berbasis Google Sites Untuk Pembelajaran Sejarah Lokal Kelas XI IPS SMA Negeri 1 Cikarang Timur - Raflie Rheznandya Ardiza; Deny Yudo Wahyudi (Cetta: Jurnal Ilmu Pendidikan, 2023)
The research that will be carried out starts from existing problems in the realm of education by looking at the importance of local history, and trying to provide solutions as a form of learning innovation. The problem faced by students at SMA Negeri 1 Cikarang Timur is knowledge of local history, especially historical evidence of the Tarumanagara Kingdom, namely the Batujaya Temple Site which is located in Karawang Regency. In answering the problems faced by local history learning, the solution that can be implemented in local history learning is the use of learning technology as a learning media innovation. Therefore, utilizing technology in learning has become mandatory. The technology used by researchers is a website based on Google Sites. This research aims to develop the Situs Percandian Batujaya Karawang (SIPERBAKA) media as a support for learning the local history of the Hindu-Buddhist kingdoms, especially the Tarumanagara Kingdom which is based in West Java for students at SMA Negeri 1 Cikarang Timur. The research method used in this research is the Research & Development method. The development of the media used can be done through various development models, one of which is the Design Thinking model. The ease in understanding the content and material on SIPERBAKA media was 48% of them said "Strongly Agree", 51% said "Agree" and 1% said "Disagree". This means that the majority of the content and materials on SIPERBAKA media are easy to understand. These results illustrate that the visual approach promoted by SIPERBAKA is able to provide clear and effective explanations to students. In conclusion, the results of this data provide evidence that the use of SIPERBAKA media is a practical and efficient choice in assisting the learning process, as well as encouraging student learning independence through the accessibility and ease of use provided.